2008
DOI: 10.1136/bjsm.2007.043422
|View full text |Cite
|
Sign up to set email alerts
|

The effect of head protection on the hearing of rugby players: Table 1

Abstract: Theoretical concerns that "ear taping" and scrum caps affect hearing of rugby players are unfounded and should not discourage their use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
5
1
Order By: Relevance
“…2 ). In addition, although wearing a helmet worsens hearing to a signifi cantly greater extent than wearing a cap in this study, hearing thresholds exceeded neither with cap nor with helmet a value of 20 dB HL and are therefore still within the range of normal hearing (i. e., hearing thresholds not greater than 20 dB HL at any frequency) [ 9 ] . Thus, we conclude that both the cap and the helmet attenuate sounds only slightly.…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…2 ). In addition, although wearing a helmet worsens hearing to a signifi cantly greater extent than wearing a cap in this study, hearing thresholds exceeded neither with cap nor with helmet a value of 20 dB HL and are therefore still within the range of normal hearing (i. e., hearing thresholds not greater than 20 dB HL at any frequency) [ 9 ] . Thus, we conclude that both the cap and the helmet attenuate sounds only slightly.…”
contrasting
confidence: 65%
“…Regardless of their minor impact on the attenuation of sounds a statistically signifi cant diff erence between cap and helmet has been found. Kieran et al [ 9 ] investigated the eff ect of head protection on the hearing of rugby players. These authors found that neither the application of adhesive tape ("ear taping") nor wearing a scrum cap showed a signifi cant drop in hearing threshold [ 9 ] .…”
mentioning
confidence: 99%
“…Many studies claim that a ski helmet usage has a proven benefit when it comes to a head protection [5][6][7][8][9]. However, the extent of this protection is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Players also claimed that headgear made them feel too hot during the games and too tight while wearing close fitting headgear [5]. Disturbance to hearing senses is another limitation faced by players who wear headgear, makes them unable to hear the instruction from the captain or teammates [6]. There were studies that investigated the effect of the protective equipment in preventing injury such as headgear used in rugby union and the result shows that it is only capable to provide limited protection and decrease on the risk of injuries.…”
Section: Introductionmentioning
confidence: 99%